Biosynthesis and characterization of multifunctional mixed oxides of ZnCr2O4/ZnCrO4 nanoparticulate from natural leaf extracts of Hibiscus Rosa Sinensis. (2021) - Mayedwa, N.; Mulaudzi-Masuku, T.; Matinise, N.; Nkosi, M
Abstract: Biological synthesis of zinc chromate mixed oxide nanoparticulate using natural leaf extracts of Hibiscus Rosa Sinensis . This is a simple, cost-effective and reproducible aqueous room temperature synthesis method to obtain spinel cubic phase ZnCr2 O4 mixed oxide nanoparticles. X-ray diffraction (XRD) confirmed nanoparticles were crystalline with particle size estimated 14 nm for ZnCr2 O4 nanoparticles annealed at 700 °C, 26 nm at 500 °C, 56 nm at 200 °C and 70 nm at room temperature (RT). High resolution- transmission electron microscope (HR-TEM) and HR-scanning electron microscope (SEM) confirmed particles size of nanoparticles is around (fparticles ) ∼14.5 ± 2 nm for HRTEM and 60–70 nm sized agglomerated cubic shaped particles for HRSEM. Fourier transform infrared spectrum (FTIR) was used for structural analysis. The band gaps calculated from UV–vis diffused reflectance (DR) are for ZnCr2 O4 mixed oxide nanoparticles at RT and annealed at 200 °C, 500 °C and 700 °C are 2.47 eV, 2.40 eV, 3.19 eV and 3.09 eV respectively. Fluorescence excitation was used to confirm band gaps of DR showing ZnCr2 O4 mixed oxide nanoparticles possess excellent photocatalytic activity.